2000
DOI: 10.1073/pnas.140212997
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Holliday junction DNA in complex with a single RuvA tetramer

Abstract: In the major pathway of homologous DNA recombination in prokaryotic cells, the Holliday junction intermediate is processed through its association with RuvA, RuvB, and RuvC proteins. Specific binding of the RuvA tetramer to the Holliday junction is required for the RuvB motor protein to be loaded onto the junction DNA, and the RuvAB complex drives the ATP-dependent branch migration. We solved the crystal structure of the Holliday junction bound to a single Escherichia coli RuvA tetramer at 3.1-Å resolution. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 31 publications
9
147
0
Order By: Relevance
“…This conformation may be preferable for Mus81 because it was reported that several studied junction-specific nucleases show preference for the DNA junctions in the open conformation (36). The proposed mechanism has a precedent: RuvA protein stabilizes HJs in a square-plane (open) conformation, facilitating RuvAB branch migration and, presumably, RuvC cleavage (37). Stimulation of hMus81 activity by hRad54 in vitro is consistent with genetic data because a functional link between Rad54 and Mus81 is documented.…”
Section: Discussionsupporting
confidence: 74%
“…This conformation may be preferable for Mus81 because it was reported that several studied junction-specific nucleases show preference for the DNA junctions in the open conformation (36). The proposed mechanism has a precedent: RuvA protein stabilizes HJs in a square-plane (open) conformation, facilitating RuvAB branch migration and, presumably, RuvC cleavage (37). Stimulation of hMus81 activity by hRad54 in vitro is consistent with genetic data because a functional link between Rad54 and Mus81 is documented.…”
Section: Discussionsupporting
confidence: 74%
“…The domains in ERCC1 and XPF are structurally similar to the tandem HhH 2 found in the prokaryotic proteins UvrC and RuvA [16,[36][37][38][39]. The DNA binding properties of the isolated HhH 2 domains of ERCC1 and XPF have been evaluated [16].…”
Section: Ercc1-xpf Focusmentioning
confidence: 98%
“…Four of these amino acids are hydrophobic residues located in domain III of E. coli RuvA and are likely to form an interface with RuvB. X-ray crystallography of the E. coli RuvA-Holliday junction complex revealed that two helix-hairpin-helix (HhH) motifs in domain II are involved in Holliday junction binding (Ariyoshi et al, 2000). The nitrogens of the main chain amides of Gly-80 and Gly-82 in the hairpin in HhH I interact with phosphate oxygens of the junction DNA through hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary structure of E. coli RuvA (α helices and β strands) is shown above the alignment and is indicated by arrows (β strands) and bold lines (α helices). Domains 1, 2, and 3 include β1 to β6, α2 to α6, and α7 to α9, respectively (Ariyoshi et al, 2000;Nishino et al, 1998;Rafferty et al, 1996). The striped bars between domains 2 and 3 indicate disordered structure.…”
Section: Resultsmentioning
confidence: 99%